Excimer lamp as an effective alternative treatment for severe alopecia areata - Tzu-Chien Hsu; Tzu-Kai Lin; Chao-Kai Hsu; Herng-Jeng Jou; Chao-Chun Yang (Wolters Kluwer Medknow Publications, 2015)
The treatment response of alopecia areata (AA) is often unpredictable. The aim of this study was to report the efficacy of an excimer lamp in treating AA. Seventeen AA patients were included. The overall response rate was 41.1%, and the satisfactory response rate was 29.4%. In patients with severe AA, the response rate was 50%. The therapeutic effect of the excimer lamp was evident by internal control. The onset of improvement occurred after 2 months, and only mild side effects were noted. Our results suggest that the 308-nm excimer lamp is a safe alternative treatment for AA, including those with severe AA.